FORMULATION AND EVALUATION OF METAMIZOLE Na TABLETS WITH DIFFERENT CONCENTRATIONS OF SWEET POTATO FLOUR (Ipomea Batatas L.) AS DISINTEGRATOR - Rizka Dianti Wahyudi; arif wijayanto (Universitas STRADA Indonesia, 2020)
Sweet potatoes have a fairly high starch content, namely 84.89%. High levels of starch can be used as a disintegrating agent in the manufacture of pharmaceutical preparations, namely tablets. The aim of this research is to determine the effect of variations in the concentration of sweet potato flour as a disintegrating agent and to determine how sweet potato flour is a candidate disintegrating agent in making tablet preparations using experimental methods in several concentrations on the properties and physical properties of Metamizole Na® tablets. Based on the results of this research, 3 formulations were made, namely formulation I (2.5%), formulation II (5%), formulation III (7.5%). The results obtained from this research indicate that formulation I is the best formulation of the other 3 formulas because formulation I is the formulation whose results in each test are closest to the positive control.